The Algerian Child And Technological Consumption: A reading Of Studies And Statistics - Bayoucef, Messaouda (Journal of Architecture and environment of child, 2022)
This study aims to present a very important topic, which is "The Algerian Child’s consumption of Technological Means"., by retracing the various Algerian studies and research on this subject; It was carried out in different national regions and wilayas. The researcher concluded that the Algerian child uses a lot of technological means and in several places (home, school, cybercafés, youth centers ...) and in a social and cultural context that encourages this cultural and informational, This intense consumption has earned him a knowledge and understanding of technology which has more of a performance and practical dimension than an informational and cultural awareness. And it had negative effects. repercussions - mostly - on the identity, values and mental and physical health of the child, This prompts us to step up efforts in the field of educating children, parents and educators about the need to instill digital culture and media literacy in young people, who are the future’s men and the country’s hope